The legitimating logic of stability: analysing the CCP's stability discourse - Sandby-Thomas, Peter (2008)
This thesis addresses the question of why the Chinese Communist Party (CCP) has remained in power since the Tiananmen Incident in 1989 by deploying the concept of political legitimacy. In this, the focus is not on whether the CCP is legitimate per se but rather on how the Party has legitimated its authority in this period. To that end, the Weberian conceptualisation of legitimation is situated within the Strategic-Relational Approach and, in so doing, allows, through the concept of "discursive selectivity", for legitimation to be reconceptualised as a dialectical relationship consisting of both material and ideational factors. The effect of this move is to provide a suitable framework in which to consider additional legitimating strategies that are employed by the CCP. Consequently, this paper moves beyond the conventional explanation of "economic performance + nationalism" to argue that the CCP's use of the stability discourse in the post-Tiananmen period has contributed to the regime's legitimation. In order to understand how this discourse has been used, a critical discourse analysis is performed on selected articles from the People's Daily published during the Beijing Spring, the "anti-Falun Gong" campaign and the "anti-Japan" demonstrations on the basis that these exceptional instances inform its usage in conventionalised slogans. This analysis found that the term "stability" took the form of an "empty signifier", making most use of positive argument schemes to project a negative Chinese future without CCP authority. Finally, this thesis concludes that, in terms of legitimation, the events in 1989 constituted a strategic moment in the formation of the stability discourse, in that the Party's hegemonic interpretation of these events allowed for this discourse to "resonate" with people in the period that has followed.